Design and study of different patterns of traction threads on the effects of traction on the vehicle - Low, Yiing Jye. (2011)
Traction device are commonly found and used in regions where snow can cause mobility problems for vehicles, during winter. Yet, in other areas such as rescue and restoration, and construction, traction devices for heavy vehicles also play an important role, because of the soft and slippery soil surface they move on. While steel traction chains meant for snow can be conveniently used for vehicles moving in mud, they remain costly, with a short lifespan and are a hassle for drivers to install them.